Structural and bone marrow stem cell biocompatibility studies of hydrogel synthesized via chemo-enzymatic route - Latfi, Ahmad Safwan Ahmad; Pramanik, Sumit; Poon, Chi Tat; Gumel, Ahmad Mohammed; Lai, Khin Wee; Annuar, Mohamad Suffian Mohamad; Pingguan-Murphy, Belinda (SAGE Publications, 2019)
Natural biopolymers have many attractive medical applications; however, complications due to fibrosis caused a reduction in diffusion and dispersal of nutrients and waste products. Consequently, severe immunocompatibility problems and poor mechanical and degradation properties in synthetic polymers ensue. Hence, the present study investigates a novel hydrogel material synthesized from caprolactone, ethylene glycol, ethylenediamine, polyethylene glycol, ammonium persulfate, and tetramethylethylenediamine via chemo-enzymatic route. Spectroscopic analyses indicated the formation of polyurea and polyhydroxyurethane as the primary building block of the hydrogel starting material. Biocompatibility studies showed positive observation in biosafety test using direct contact cytotoxicity assay in addition to active cellular growth on the hydrogel scaffold based on fluorescence observation. The synthesized hydrogel also exhibited (self)fluorescence properties under specific wavelength excitation. Hence, synthesized hydrogel could be a potential candidate for medical imaging as well as tissue engineering applications as a tissue expander, coating material, biosensor, and drug delivery system.